Isobolographic analysis of co-administration of two plant-derived antiplasmodial drug candidates, cryptolepine and xylopic acid, in Plasmodium berghei - Ameyaw, Elvis O. (Malar J, 2018)
BACKGROUND: Increasing resistance to current anti-malarial therapies requires a renewed effort in searching for alternative therapies to combat this challenge, and combination therapy is the preferred approach to address this. The present study confirms the anti-plasmodial effects of two compounds, cryptolepine and xylopic acid and the relationship that exists in their combined administration determined. METHODS: Anti-plasmodial effect of cryptolepine (CYP) (3, 10, 30 mg kg(−1)) and xylopic acid (XA) (3, 10, 30 mg kg(−1)) was evaluated in Plasmodium berghei-infected male mice after a 6-day drug treatment. The respective doses which produced 50% chemosuppression (ED(50)) was determined by iterative fitting of the log-dose responses of both drugs. CYP and XA were then co-administered in a fixed dose combination of their ED(50)s (1:1) as well as different fractions of these combinations (1/2, 1/4, 1/8, 1/16 and 1/32) to find the experimental ED(50) (Z(exp)). The nature of interaction between cryptolepine and xylopic acid was determined by constructing an isobologram to compare the Z(exp) with the theoretical ED(50) (Z(add)). Additionally, the effect of cryptolepine/xylopic acid co-administration on vital organs associated with malarial parasiticidal action was assessed. RESULTS: The Z(add) and Z(exp) were determined to be 12.75 ± 0.33 and 2.60 ± 0.41, respectively, with an interaction index of 0.2041. The Z(exp) was significantly (P < 0.001) below the additive isobole indicating that co-administration of cryptolepine and xylopic acid yielded a synergistic anti-plasmodial effect. This observed synergistic antiplasmodial effect did not have any significant deleterious effect on the kidney, liver and spleen. However, the testis were affected at high doses. CONCLUSION: The co-administration of cryptolepine and xylopic acid produces synergistic anti-malarial effect with minimal toxicity.